The Influence of Council Structure and IndependenceThe Council on Corporate Financial Performance: A Systematic Literature Review - Mila Failasufa; Mukhtaruddin Mukhtaruddin (Escalate : Economics and Business Journal, 2026)
This study aims to collect and analyze the results of previous research related to the influence of board structure and board independence on the company's financial performance. We analyzed 22 research articles published between 2020-2025. The results show that good board structures (such as the right number of members, gender diversity, and special committees) as well as independent boards can generally improve a company's financial performance (measured by ROA, ROE, and Tobin's Q). However, these results are not always the same in every company. Factors such as industry type, country regulations, and market conditions can affect how much influence the board has on performance. The most commonly used theory to explain this relationship is Agency Theory. This study provides advice for companies in drafting effective boards and for future research to pay more attention to factors that can strengthen or weaken these relationships.